Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai Kejujuran pada Siswa SMP Islam Ngadirejo - Muchamad Iqbal Hanafi; H.Ahmad Zuhdi; Salis Irvan Fuadi (Moral : Jurnal kajian Pendidikan Islam, 2025)
The purpose of this study was to understand the role of Islamic Religious Education teachers in instilling values ​​in students of SMP Islam Ngadirejo, Temanggung and to identify factors that support and inhibit Islamic Religious Education teachers' efforts to instill honesty values ​​in students at SMP Islam Ngadirejo, Temanggung. This study used a qualitative field approach, namely a method in which researchers are directly involved in the research location to obtain in-depth data regarding the events or problems being studied. The results of the study are that the role of teachers plays a crucial role in the world of education, especially in instilling honesty values. This is considered important because teachers interact directly with students during the teaching and learning process, which is a strategic moment for teachers to instill honesty values ​​in students. The formulation of the problem in this thesis is: 1. What is the role of Islamic Religious Education teachers in instilling the value of honesty? 2. How is the implementation of Islamic Religious Education teachers in instilling the value of honesty to students at SMP Islam Ngadirejo, Temanggung? 3. What are the supporting and inhibiting factors of Islamic Religious Education teachers in instilling the value of honesty to students at SMP Islam Ngadirejo, Temanggung.